Luxury Meets Sustainability: Eco Tourism Strategy At Lampung Marriott Resort & Spa - Manan, Mohammad Athian; Sejati, Hiro; Mufahamah, Euis (JELAJAH: Journal of Tourism and Hospitality, 2025)
Sustainable tourism is a crucial aspect in maintaining the attractiveness of tourist destinations while minimizing environmental and economic impacts. This study aims to analyze the influence of tourist satisfaction, environmental impact, and destination attractiveness on the sustainability of tourism at Lampung Marriott Resort & Spa. This research employs a quantitative approach using a simple random sampling method, involving 100 tourists visiting the destination. Data were collected through questionnaires and analyzed using regression tests with SPSS version 23 to examine the relationships between the research variables. The findings reveal that tourist satisfaction, environmental impact, and destination attractiveness have a significant positive effect on tourism sustainability. High tourist satisfaction indicates that the services and facilities provided meet visitors’ expectations. Effective environmental management contributes to maintaining long-term destination appeal, while destination attractiveness, including natural beauty and cultural diversity, plays a key role in attracting more visitors. This study concludes that achieving tourism sustainability requires continuous improvement in service quality, sustainable environmental management strategies, and innovation in destination development. Therefore, tourism managers should enhance visitor experiences and implement sustainability principles to maintain long-term competitiveness.